Formation of fluid lamellar phase and large unilamellar vesicles with octadecyl methyl sulfoxide/cholesterol mixtures - Cui, Zhong-Kai (Langmuir : the ACS journal of surfaces and colloids, 2010)
Systems composed of a monoalkylated amphiphile and a sterol have been shown to form stable liquid-ordered (lo) lamellar phases; these include negatively charged mixtures of unprotonated palmitic acid/cholesterol (Chol) or cholesterol sulfate (Schol) and mixtures of positively charged cetylpyridinium chloride/Schol. Large unilamellar vesicles (LUVs) could be formed by these systems, using conventional extrusion methods. The passive permeability of these LUVs was drastically limited, a phenomenon associated with the high sterol content. In the present paper, we showed that octadecyl methyl sulfoxide (OMSO), a neutral monoalkylated amphiphile, can form, in the presence of cholesterol, LUVs that are stable at room temperature. Differential scanning calorimetry, infrared spectroscopy, and nuclear magnetic resonance spectroscopy of deuterium were used to characterize the phase behavior of OMSO/Chol mixtures. A temperature-composition diagram summarizing the behavior of the OMSO/Chol system is proposed; it includes a eutectic with an OMSO/Chol molar ratio of 5/5. It is found that the fluid phase observed at temperature higher than 43 degrees C is metastable at room temperature, and this situation allows extruding these mixtures to form stable LUVs at room temperature. This distinct behavior is associated with the strong H-bond capability of the sulfoxide group. The properties associated with this neutral formulation expand the potential of these non-phospholipid liposomes for applications in several areas such as drug delivery